Ambulatory total hip arthroplasty: Causes for failure to launch and associated risk factors. (1st September 2022) - Rodriguez, Samuel; Shen, Tony S.; Lebrun, Drake G.; Della Valle, Alejandro G.; Ast, Michael P.; Rodriguez, Jose A.
Abstract : Aims: The volume of ambulatory total hip arthroplasty (THA) procedures is increasing due to the emphasis on value-based care. The purpose of the study is to identify the causes for failed same-day discharge (SDD) and perioperative factors leading to failed SDD. Methods: This retrospective cohort study followed pre-selected patients for SDD THA from 1 August 2018 to 31 December 2020. Inclusion criteria were patients undergoing unilateral THA with appropriate social support, age 18 to 75 years, and BMI < 37 kg/m 2 . Patients with opioid dependence, coronary artery disease, and valvular heart disease were excluded. Demographics, comorbidities, and perioperative data were collected from the electronic medical records. Possible risk factors for failed SDD were identified using multivariate logistic regression. Results: In all, 278 patients were identified with a mean age of 57.1 years (SD 8.1) and a mean BMI of 27.3 kg/m 2 (SD 4.5). A total of 96 patients failed SDD, with the most common reasons being failure to clear physical therapy (26%), dizziness (22%), and postoperative nausea and vomiting (11%). Risk factors associated with failed SDD included smokers (odds ratio (OR) 6.24; p = 0.009), a maximum postoperative pain score > 8 (OR 4.76; p = 0.004), and procedures starting after 11 am (OR 2.28; p = 0.015). A higher postoperative tolerable pain goal (numerical rating scale 4 to 10) was found to be associated with successful SDD (OR 2.7; p = 0.001). Age, BMI, surgical approach, American Society of Anesthesiologists grade, and anaesthesia type were not associated with failed SDD. Conclusion: SDD is a safe and viable option for pre-selected patients interested in rapid recovery THA. The most common causes for failure to launch were failing to clear physical thereapy and patient symptomatology. Risk factors associated with failed SSD highlight the importance of preoperative counselling regarding smoking cessation and postoperative pain to set reasonable expectations. Future interventions should aim to improve patient postoperative mobilization, pain control, and decrease symptomatology. Cite this article: Bone Jt Open  2022;3(9):684–691.